Increase of Curie point of BaTiO3 ceramics by stoichiometry, point defects and doping processing - Jianquan Qi; Hui Fang; Jiang Wang; Xiumei Han; Zizhou Liang; Jin Ma; Xunzhong Shang; Liuting Gu; Wanping Chen (Journal of Advanced Dielectrics)
The Curie point of barium titanate (BaTiO3) has been a focal point of research since the discovery of its ferroelectric properties. Exploring methods to elevate the Curie point without relying on Pb as a dopant presents fresh opportunities for lead-free dielectric and/or piezoelectric materials. It is essential to avoid introducing ions like K[Formula: see text] and Na[Formula: see text], which could jeopardize the functional ceramic characteristics. This study delves into the stoichiometry of barium titanate, examining how impurities, point defects and doping techniques influence its Curie point, focus on the potential of doping and processing to enhance this property. BaTiO3 nanopowders were synthesized directly with varying Ba:Ti ratios in an ethanol–water solution at 60∘C, followed by sintering at 1280∘C and characterization through dielectric spectroscopy. A comparison was made with samples doped with Si, vapor-doped with Bi and vapor-doped with Pb. Results revealed that even minimal Si doping could boost the ferroelectric properties and elevate the Curie point, while vapor-doping with trace amounts of PbO or Bi2O3 significantly increased the Curie point, particularly in samples with higher Ti content. The impact of vapor dopants of PbO and Bi2O3 was similar, with a nominal doping level of 1[Formula: see text]mol% shifting the Curie point above 140∘C. Notably, in samples with a Ba:Ti ratio of 0.95 vapor-doped with PbO, the Curie point rose to 146∘C, a notable increase of 16∘C, surpassing the traditional doping efficiency. This study offers fresh insights into enhancing the Curie point of barium titanate-based materials, exploring the intricate connections among chemical stoichiometry, dopants, point defects and dielectric properties. It highlights the significant influence of chemical composition, impurities, defects and doping strategies on the dielectric characteristics of barium titanate.